2019
DOI: 10.1177/2309499019848085
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of frontal plane lower limb movement during walking in patients with knee osteoarthritis of varying severity

Abstract: This study aimed to investigate the effect of knee joint structural destruction on frontal plane hip and ankle joint kinematics and kinetics during the stance phase of walking in patients with differing severities of knee osteoarthritis (KOA). Methods: An early KOA group consisted of eight subjects with bilateral knee Kellgren-Lawrence (KL) scale scores of 1 or 2. An established KOA group comprised nine subjects (18 knees) with KL scores of 3 or 4. To measure walking, the data were obtained using the motion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The significant correlation between femoral anteversion, hamstring muscle length, Q angle (dynamic), and tibial torsion with NRS pain scale. BMI (mean ± SD) = 27.97 ± 8.70 kg/m2 - Femoral anteversion (mean ± SD) = 12.15 ± 12.02° - Hamstring muscle length (mean ± SD) = 280 ± 20.13 mm - Q angle (mean ± SD) static = 18.5 ± 16.26° Q angle dynamic (mean ± SD) = 24 ± 16.97° - Navicular drop height (mean ± SD) = 7.5 ± 6.36 mm - Tibial torsion (mean ± SD) = 8.5 ± 7.36° 5 Fukaya T et al, Japan, 2019 [ 29 ] n = 8 (3 men and 5 women), recorded a KL scale score of 1–2 n = 9 (3 men and six women), recorded a KL scale score of 3–4 CSS To investigate the effect of structural destruction of the knee joint on frontal plane hip and ankle joint kinematics and kinetics during the stance phase of walking in individuals with differing severities of knee OA. WOMAC and KL Vicon Mx2 Camera system Three AMTI force plates In the Knee OA group with KL 3–4, the hip joint was significantly abducted and the knee joint had significantly greater varus positioning during the stance phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant correlation between femoral anteversion, hamstring muscle length, Q angle (dynamic), and tibial torsion with NRS pain scale. BMI (mean ± SD) = 27.97 ± 8.70 kg/m2 - Femoral anteversion (mean ± SD) = 12.15 ± 12.02° - Hamstring muscle length (mean ± SD) = 280 ± 20.13 mm - Q angle (mean ± SD) static = 18.5 ± 16.26° Q angle dynamic (mean ± SD) = 24 ± 16.97° - Navicular drop height (mean ± SD) = 7.5 ± 6.36 mm - Tibial torsion (mean ± SD) = 8.5 ± 7.36° 5 Fukaya T et al, Japan, 2019 [ 29 ] n = 8 (3 men and 5 women), recorded a KL scale score of 1–2 n = 9 (3 men and six women), recorded a KL scale score of 3–4 CSS To investigate the effect of structural destruction of the knee joint on frontal plane hip and ankle joint kinematics and kinetics during the stance phase of walking in individuals with differing severities of knee OA. WOMAC and KL Vicon Mx2 Camera system Three AMTI force plates In the Knee OA group with KL 3–4, the hip joint was significantly abducted and the knee joint had significantly greater varus positioning during the stance phase.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the knee abduction moment can be reduced. As the severity of Knee OA increases, the tendency of hip abduction positions also increases [ 29 ]. The abduction position of the hip joint produces a larger abduction moment on the knee joint.…”
Section: Discussionmentioning
confidence: 99%
“…Each group contained 15 people. For the purposes of this study, K–L grades 3 and 4 were considered as a single group ( Fukaya et al, 2019 ; Ismailidis et al, 2020 ). The selected patients had confirmed imaging findings indicative of primary KOA.…”
Section: Methodsmentioning
confidence: 99%
“…The COP mediolateral deviation was defined as the mediolateral axial coordinates of the COP relative to a line connecting the Gait parameters in the stance phase were normalized to 100% and averaged over three trials. Loading response (16% of the stance: LR), midstance (50% of the stance: MS), and terminal stance (83% of the stance: TS) during the stance phase were the analysis points 10,14) . The IAMF and COM coordinates were calculated based on the Plug-in Gait Full Body Model, and the TLD, the asymmetrical ratios of the UTS and LTS, the center of the foot coordinates, and the COP mediolateral deviation were calculated using analysis programming software (Body Builder; Vicon Motion Systems, Ltd., Oxford, UK).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Choi et al 8 ) claimed that the external ankle varus moment during gait in patients with medial ankle osteoarthritis is a mechanical factor that causes varus of the talus, and they reported that patients with a lower medial longitudinal arch had a greater varus moment. Furthermore, gait analysis in patients with knee osteoarthritis 9 , 10 ) has revealed that the IAMF is associated with external knee adduction moment, and the IAMF is considered an important factor in the progression of knee osteoarthritis. Thus, IAMF imbalance is considered a factor that increases mechanical stress on the lower extremities and negatively affects the local alignment.…”
Section: Introductionmentioning
confidence: 99%